2019
DOI: 10.1103/physrevmaterials.3.110301
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of chemically doped graphene

Abstract: Chemical doping of graphene is the most robust way of modifying graphene's electronic properties. We review here the results obtained so far on the electronic structure and transport properties of chemically-doped graphene, focusing on the results obtained with scanning tunneling micropscopy/spectroscopy (STM/S), angle-resolved photoemission spectroscopy (ARPES), and magnetoresistance (MR) measurements. The majority of the results reported have been obtained on nitrogendoped samples, but boron-doped graphene h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 144 publications
2
38
0
Order By: Relevance
“…Doping graphene has become a well-established route to tailoring the material properties to the respective applications. First experiments using mainly nitrogen and boron [1,2] that started soon after the first experimental studies of pristine graphene [3,4] have showcased the extraordinary properties of graphene. Now the range of heteroatoms, both in theory and applications, has increased including among others phosphorus [5], sulfur [6], fluoride [7] and potassium [8].…”
Section: Introductionmentioning
confidence: 99%
“…Doping graphene has become a well-established route to tailoring the material properties to the respective applications. First experiments using mainly nitrogen and boron [1,2] that started soon after the first experimental studies of pristine graphene [3,4] have showcased the extraordinary properties of graphene. Now the range of heteroatoms, both in theory and applications, has increased including among others phosphorus [5], sulfur [6], fluoride [7] and potassium [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-doped graphene-like nanostructures (hereafter: N-graphene) have attracted significant scientific attention because of their good electronic properties [ 1 , 2 , 3 , 4 ] which allows their possible application in electrochemical devices such as fuel cells, super-batteries, and supercapacitors [ 5 , 6 , 7 ]. As early as 2011, Zhang and Xia provided a feasible explanation for the superior properties of such materials in fuel cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Doped graphene materials (mono, binary, and ternary) with metal and nonmetal have been modeled and studied extensively 42–51 . Doping foreign material into graphene's honeycomb structure distorts its structural and electronic homogeneity, making it vulnerable to active species for ORR and OER 52–54 . The second technique is to calculate the energy of the intermediate steps with different configurations using density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49][50][51] Doping foreign material into graphene's honeycomb structure distorts its structural and electronic homogeneity, making it vulnerable to active species for ORR and OER. [52][53][54] The second technique is to calculate the energy of the intermediate steps with different configurations using density functional theory (DFT). Nørskov et al 55 reported a detailed mechanism by unifying the common processes, assisted by the heterogeneous catalyst.…”
mentioning
confidence: 99%